Faktor-Faktor yang Berhubungan dengan Perilaku Seks Pranikah pada Remaja di SMA Negeri 2 Sarolangun Tahun 2022 - Dewi Reknowati; Desy Susanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
According to IDHS (2012), the prevalence of pre-marital sex cases was 14.6% among young women aged 15-19 years. The reasons for premarital sexual intercourse were mostly due to curiosity/curiosity (57.5%), it just happened to women (38%), and was forced by partners (12.6%) to women. Â The aim of the research is to find out the factors related to premarital sexual behavior in adolescents at SMA Negeri 2 Sarolangun in 2022. This research is analytic in nature with a cross sectional research design. The research was carried out at SMA Negeri 2 Sarolangun and was carried out in June 2022. The population for this research was all students of class X and XI SMA Negeri 2 Sarolangun as many as 243 people. The sample of this research is 70 people. The data analysis used was univariate and bivariate analysis. Â The results showed that there was a relationship between family support and premarital sex behavior in adolescents with a p-value = 0.000, there was a relationship between information sources and premarital sex behavior in adolescents with a p-value of 0.003, and there was a relationship between knowledge and premarital sex behavior in adolescents. adolescents with a p-value of 0.001.